Liraglutide relieves myocardial damage by promoting autophagy via AMPK-mTOR signaling pathway in zucker diabetic fatty rat. (15th June 2017) - Zhang, Ya; Ling, Yuanna; Yang, Li; Cheng, Yanzhen; Yang, Pingzhen; Song, Xudong; Tang, Huixiong; Zhong, Yongkang; Tang, Lu; He, Shangfei; Yang, Shuangli; Chen, Aihua; et al.
Abstract: Liraglutide, a glucose-lowering agent used to treat type 2 diabetic mellitus is reported to exert cardioprotective effects in clinical trials and animal experiments. However, the cardioprotective mechanism of liraglutide on diabetic cardiomyopathy has not been fully illustrated. The present study was performed to investigate whether liraglutide alleviates diabetic myocardium injury by promoting autophagy and its underlying mechanisms. Our results show that liraglutide significantly reduced the levels of creatine kinase (CK) and lactate dehydrogenase (LDH), improved left ventricular functional status and alleviated myocardial fibrosis in the Zucker diabetic fatty (ZDF) rat model. Liraglutide also mitigated high glucose-induced injury in NRCs. However these effects were partly reversed by the autophagic inhibitor chloroquine (CQ). Liraglutide promoted myocardial autophagy in the vivo and in the vitro models. Furthermore, liraglutide-induced enhancement of autophagy was related to increased AMPK phosphorylation and decreased mTOR phosphorylation, which was partially abolished by the AMPK inhibitor compound C (Comp C). Collectively, our data provide evidence that liraglutide mediated diabetic myocardium injury by promoting AMPK-dependent autophagy. Highlights: Liraglutide alleviates diabetic myocardium injury. The promotion of autophagy is one of the cardioprotective mechanisms of liraglutide. The promotion of autophagy by liraglutide is dependent on AMPK signaling pathway.